Tranylcypromine‐Based LSD1 Inhibitors: Structure‐Activity Relationships, Antiproliferative Effects in Leukemia, and Gene Target Modulation. (14th February 2020) - Fioravanti, Rossella; Romanelli, Annalisa; Mautone, Nicola; Di Bello, Elisabetta; Rovere, Annarita; Corinti, Davide; Zwergel, Clemens; Valente, Sergio; Rotili, Dante; Botrugno, Oronza A.; Dessanti, Paola; Vultaggio, Stefania; et al.
Abstract: Abstract : LSD1 is a lysine demethylase highly involved in initiation and development of cancer. To design highly effective covalent inhibitors, a strategy is to fill its large catalytic cleft by designing tranylcypromine (TCP) analogs decorated with long, hindered substituents. We prepared three series of TCP analogs, carrying aroyl‐ and arylacetylamino (1 a –h ), Z ‐amino acylamino (2 a –o ), or double‐substituted benzamide (3 a –n ) residues at the C4 or C3 position of the phenyl ring. Further fragments obtained by chemical manipulation applied on the TCP scaffold (compounds 4 a –i ) were also prepared. When tested against LSD1, most of 1 and 3 exhibited IC50 values in the low nanomolar range, with 1 e and 3 a, d, f, g being also the most selective respect to monoamine oxidases. In MV4‐11 AML and NB4 APL cells compounds 3 were the most potent, displaying up to sub‐micromolar cell growth inhibition against both cell lines (3 a ) or against NB4 cells (3 c ). The most potent compounds in cellular assays were also able to induce the expression of LSD1 target genes, such as GFI‐1b, ITGAM, and KCTD12, as functional read‐out for LSD1 inhibition. Mouse and human intrinsic clearance data highlighted the high metabolic stability of compounds 3 a, 3 d and 3 g . Further studies will be performed on the new compounds 3 a and 3 c to assess their anticancer potential in different cancer contexts. Abstract : Some TCP for LSD : Lysine specific demethylase 1 (LSD1) is heavily involved in the initiation and progression of cancer. Through an X‐ray‐driven drug discovery process, we identified some tranylcypromine (TCP)‐based compounds 1 –4 . Among them, 1 –3 were found to be active against LSD1 in the sub‐micromolar/low nanomolar range. When tested in MV4‐11 AML and NB4 APL cells, 3 a and 3 c were the most potent to arrest proliferation and induced target genes under the control of LSD1 in cells. These compounds will be further validated in different cancer contexts.